Development of a Digital Marketing Based Business Model at the Kurdut Garage Workshop in Pematangsiantar City - Lenny Dermawan Sembiring; Kevin Indajang; Eliza Arshandy; Juan Anastasia Putri; Fitria Halim; Acai Sudirman (I-Com: Indonesian Community Journal, 2024)
The development of a digital marketing-based business model at the Kurdut Garage Workshop in Pematangsiantar has a very important urgency in facing the ever-growing era of digitalization. The method used in implementing this activity is through lectures and FGD (group discussion forum). The stages of implementing this event include explaining the fundamentals of being an entrepreneur, explaining several problems that entrepreneurs often face, then continuing with discussions related to developing new businesses. After the service activities are completed, follow-up interviews are conducted regarding the impact of implementing the service activities. By the results of the interview, it is known that the understanding of Kurdut Garage Workshop business owners regarding knowledge of the use of digital marketing has increased by 90%. The use of digital media is useful and can increase understanding and skills for partners. Therefore, it is recommended that sustainable methods of mentoring partners can be used as a solution to increase business size and also function as a means of company adaptation to increase business scale.